1981
DOI: 10.1021/ja00392a029
|View full text |Cite
|
Sign up to set email alerts
|

Addition of aromatic thiols to conjugated cycloalkenones, catalyzed by chiral .beta.-hydroxy amines. A mechanistic study of homogeneous catalytic asymmetric synthesis

Abstract: Reactions between aromatic thiols and conjugated cycloalkenones afford optically active 3-arylthiocycloalkanones, when chiral bases are used as catalysts. This paper reports a detailed investigation into the mechanism of this catalytic asymmetric synthesis. The reaction has been performed under a variety of conditions. Catalysts containing the 0-hydroxy amine moiety (cinchona and ephedra alkaloids) give higher reaction rates and higher enantiomeric excesses (ee's) (up to 75%) than catalysts without a hydroxyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
185
1
6

Year Published

1996
1996
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 447 publications
(197 citation statements)
references
References 8 publications
5
185
1
6
Order By: Relevance
“…For all receptors we found that the reaction is essentially complete after 15 hours. This result is in agreement with similar findings of Hiemstra et al 12 for the alkaloid catalysts. For most receptors the optical purity values of the reaction products were negligible.…”
Section: Scheme 2 Recueil Des Travaux Chimiques Des Pays-bas 115 /7supporting
confidence: 94%
“…For all receptors we found that the reaction is essentially complete after 15 hours. This result is in agreement with similar findings of Hiemstra et al 12 for the alkaloid catalysts. For most receptors the optical purity values of the reaction products were negligible.…”
Section: Scheme 2 Recueil Des Travaux Chimiques Des Pays-bas 115 /7supporting
confidence: 94%
“…Wynberg himself performed a detailed mechanistic study of the cinchonidine-catalyzed addition of thiophenols to cyclic enones (Scheme 16). [66] A bifunctional activation mode of the catalyst was proposed. The basic catalyst is supposed to deprotonate the thiol (58) as well as the electrophile to hydrogen bond to the catalyst β-hydroxy group and a ternary complex, formed by the protonated catalytic base, the thiolate anion and the enone, accounts for the transition state (60).…”
Section: 4-conjugate Additions Of Heteroatom Nucleophilesmentioning
confidence: 99%
“…In classic methods, this reaction catalyzed by strong bases such as alkali metal alkoxides [6], hydroxides [7] and amines [8]. The employment of these strong bases and acids in these reactions [9], however, leads to two main problems affecting the environment; the necessity to dispose of huge amounts of organic waste due to formation of undesirable side products resulting from polymerization, bis-addition and self condensation, and total dissolved salts formed following the neutralization of soluble bases with acids.…”
Section: Introductionmentioning
confidence: 99%